Emerging Bond Market In Thailand Problem And Prospects - P. Gupta, Jyoti; I. M. Pandey, I. M. Pandey; Titapong Techa-umponkul, Titapong Techa-umponkul (Asian Academy of Management (AAM), 1996)
The Thai economic system has changed tremendously during the past 5-6 years because of its rapid growth. It is imperative for Thailand to adjust herself in order to withstand greater challenges that will be forthcoming as a result of deregulation of financial markets worldwide. With fast modernization of information and communication of technology, international money and capital markets have become integrated as financial systems worldwide, and they strive to achieve efficient use of resources.